Esensi Bersekolah bagi Siswa Berisiko di Sekolah Menengah Kejuruan (SMK) - Listiara, Anita; Alsa, Asmadi (Faculty of Psychology, Universitas Gadjah Mada, 2011)
The purpose of this phenomenological study was to describe and to find out the structural essence of school experience from the perspective of students at risk in vocational high school. This study also explored their achievement goals. A semistructured interview guide was utilized to gaining data from five participants. The application of criterion sampling offered the researcher access to in-depth information on the target topic recorded from the perspective of a specific group of participants who have considerable experience with the phenomenon.The results focused on the following points: (a) the specific and general themes of school experience; (b) the essence of school experience; and (c) the variation of their achievement goal. The essence of school experience is involuntary involvement. The school learning is perceived as a boredom situation. Productive subject matters or practices as thespecific curriculum of vocational high school were valued tiring and wasting time.From the perspective of the achievement goal theory, there are several goals which motivate the participants tostay and to continue their study, for instance: getting a job, achieving good exam scores, exploring and learning more subjects, avoiding parents punishment, avoiding of feeling ashamed andincompetence from others, and being as equal as others.